Configuration and organization of Primary Health Care regarding actions to promote infant food and nutrition in a city located in the Zona da Mata of Minas Gerais - Serafim, Tatiane Cristina; Donato, Sara Fassarella; Gaspar, Bernardo Melo; Martins, Felipe Oliveira; Ribeiro, Victor Emanuel; Bicalho, Mateus Capobiango; Alves, Abel Mendonça; Vechi, Marina Alves; Oliveira, Mikelen de; Parreiras, Emanuelle Emília Ferreira; Santos, Carolina Araujo dos; Araújo, Raquel Maria Amaral; et al. (Ciência e Natura, 2022)
The study analyzed the promotion of infant food and nutrition for children under two years in the Primary Health Care in a city located in Minas Gerais. An exploratory and descriptive study interviewing managers, coordinating nurse, community health workers and mothers of registered children. The data were analyzed using the Shapiro-Wilk normality test and Fisher's exact test, Pearson's chi-square test and simple Student t test. The city did not implement the Strategy Amamenta e Alimenta Brasil. Strategy for Family Health performed childcare, but in an irregular or incomplete way. The main difficulties were low adherence by mothers and work overload by nurses. SISVAN's nutritional diagnosis reports are not used.55.6% of mothers participate in the childcare. 33.3% of mothers received guidance on breastfeeding before and after the baby was born. 22.2% received it during prenatal care and 5.6% received it only after the baby was born. Half of the mothers received guidance on healthy complementary feeding. No significant associations were found for the participation of mothers and the variables maternal education, maternal age, having an only child, being an adolescent mother. Mothers should be advised on the approach of the units to monitor the child's growth and development, preventing health problems.